Effects of hot plate and autoclave on pH of nutrient media - Pasqual, Moacir; Ribeiro, Valtemir Goncalves; de Barros, Inacio (Pesquisa Agropecuaria Brasileira, 1992)
The purpose of the present work was to determine the pH variations by hot plate and autoclave used for preparation and sterilization of nutrient media. The treatments were 'MS' media (4/4, 3/4, 2/4, 1/2 and 0/4) and agar concentrations (0, 2, 4, 6, 8 e 10 g/l). The pH was adjusted at 5.7 and it was registred after melting of agar on hot plate and after autoclaving at 120oC for 20 minutes. Hot plate and autoclave induce pH variations. The pH variation is very little when agar is absent. The effects of hot plate and autoclave are similar on pH variation at high agar concentrations (8 and 10 g/l). There is an increasing reduction of pH on hot plate and a decreasing reduction of pH in autoclave when the 'MS' media length increase. The pH change 0.3-0.5 units to average, and the highest variation is 0.8 units.